Urinary incontinence in the puerperium and its impact on the health-related quality of life La incontinencia urinaria en periodo de posparto y su impacto en la calidad de vida relacionada a salud A incontinência urinária no puerpério e o impacto na qualidade de vida relacionada à saúde - Lígia da Silva Leroy; Maria Helena Baena de Moraes Lopes (Universidade de São Paulo, 2012)
This case-control study evaluated whether UI in the puerperium compromises the health-related quality of life (HRQoL) and if so, in which aspects. The study included 344 women (77 case group and 267 control group) up to 90 days postpartum, who were attended the Obstetrics Outpatient Clinic of a public teaching hospital, for the postpartum follow up consultation. A socio-demographic and clinical data questionnaire formulated and validated for the study, the International Consultation on Incontinence Questionnaire - Short-Form (ICIQ-SF), the King's Health Questionnaire (KHQ) and the Medical Outcomes Study 36 - Item Short Form Health Survey (SF-36), were applied. The mean score of the ICIQ-SF was 13.9 (SD: 3.7). The case group presented high mean scores in the domains Impact of the Incontinence, Emotions, Daily Activity Limitations and Physical Limitations, of the KHQ. The groups differed significantly in the domains Physical Aspects, Pain, General Health Status, Vitality, Social Aspects and Mental Health of the SF-36. It is concluded that UI significantly affects the physical and mental health of puerperae. Estudio caso-controle ha evaluado se la incontinencia urinaria posparto afecta la calidad de vida relacionada a salud y en que aspectos. Serán incluidas 344 mujeres (77 casos y 267 controles) hasta 90 días posparto que asistieron a la Clínica de Obstetricia de un hospital de público y de enseñanza. Fue aplicado cuestionario formulado y validado, el "International Consultation on Incontinence Questionnaire - Short -Form" (ICIQ-SF), "King´s Health Questionnaire" (KHQ) y "Medical Outcomes Study 36 - Item Short Form Health Survey" (SF-36). La media del ICIQ-SF fue 13,9 (DP: 3,7). Casos tenían altos puntajes en los dominios del Impacto de la Incontinencia, Emociones, Limitaciones de las Actividades Diarias y Limitaciones Físicas del KHQ. Los grupos presentaron diferencias significativamente en los dominios Aspectos Físicos, Dolor, Estado General de la Salud, Vitalidad, Aspectos Sociales y Salud Mental del SF-36. Se concluyó que la incontinencia urinaria afecta de manera significativa la salud física y mental de las madres. Trata-se de estudo caso-controle que avaliou se a incontinência urinária (IU) no puerpério compromete a qualidade de vida relacionada à saúde (QVRS) e em quais aspectos. Incluíram-se 344 puérperas (77 casos e 267 controles) com até 90 dias pós-parto, que compareceram ao ambulatório de obstetrícia de um hospital público e de ensino, para revisão pós-parto. Aplicou-se questionário formulado e validado para o estudo, o International Consultation on Incontinence Questionnaire - Short -Form (ICIQ-SF), o King´s Health Questionnaire (KHQ) e o Medical Outcomes Study 36 - Item Short Form Health Survey (SF-36). O escore médio do ICIQ-SF foi 13,9 (dp=3,7). Casos apresentaram pontuação média elevada nos domínios impacto da incontinência, emoções, limitações de atividades diárias e limitações físicas do KHQ. Os grupos diferiram significativamente nos domínios aspectos físicos, dor, estado geral de saúde, vitalidade, aspectos sociais e saúde mental do SF-36. Conclui-se que a IU afeta significativamente a saúde física e mental de puérperas.